The Effect of Promotion Strategy through Social Media on Purchase Decisions Mediated By Word Of Mouth Marketing - Dwi Bhakti Iriantini; Soemaryono Soemaryono; Wiwik Herawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine: (1) The effect of promotional strategies through social media on purchasing decisions (2) The effect of promotional strategies through social media on word of mouth marketing (3) The influence of word of mouth marketing on the decision to purchase (4)the effect of promotional strategies through social media mediated by word of mouth marketing on the purchasing decisions of Make Over cosmetics in the city of Surabaya. This research design is a survey research. The population in this study were consumers of Make Over cosmetic products in the city of Surabaya. The sampling technique in this study used purposive sampling with a total sample of 200. The data collection technique used a questionnaire that had been tested for validity and reliability. Data analysis techniques used to answer the research hypothesis are regression test, path analysis (path analysis), and Sobel test. The results of the study have a positive and significant influence.